2023
DOI: 10.1136/bmjopen-2022-061023
|View full text |Cite
|
Sign up to set email alerts
|

Optimal duration of antibiotic treatment for community-acquired pneumonia in adults: a systematic review and duration-effect meta-analysis

Abstract: ObjectivesTo find the optimal treatment duration with antibiotics for community-acquired pneumonia (CAP) in adults.DesignSystematic review and duration-effect meta-analysis.Data sourcesMEDLINE, Embase and CENTRAL through 25 August 2021.Eligibility criteriaAll randomised controlled trials comparing the same antibiotics used at the same daily dosage but for different durations for CAP in adults. Both outpatients and inpatients were included but not those admitted to intensive care units. We imposed no date, lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…However, the conclusions are tempered by the small number of studies and the potential for bias. Additional research is necessary, especially for patients with severe illness [ 42 ]. This study does not provide sufficient evidence to support the superiority of shorter antibiotic treatment durations over longer ones.…”
Section: Discussionmentioning
confidence: 99%
“…However, the conclusions are tempered by the small number of studies and the potential for bias. Additional research is necessary, especially for patients with severe illness [ 42 ]. This study does not provide sufficient evidence to support the superiority of shorter antibiotic treatment durations over longer ones.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 Recent meta-analyses of randomised controlled trials (RCTs) have also demonstrated that a duration of therapy of 7 days or shorter is equivalent to 7 to 14 days of antibiotic therapy, which was historically considered standard for CAP. 12 , 27 - 29 Shortening the standard duration has many potential benefits including a reduced risk of antibiotic-associated harms (including adverse events and antimicrobial resistance), improved adherence to therapy, and lower healthcare costs. 27 Longer durations of therapy are recommended for complicated infections (e.g.…”
Section: Can the Duration Of Antimicrobial Therapy Be Shortened?mentioning
confidence: 99%
“… 12 , 27 - 29 Shortening the standard duration has many potential benefits including a reduced risk of antibiotic-associated harms (including adverse events and antimicrobial resistance), improved adherence to therapy, and lower healthcare costs. 27 Longer durations of therapy are recommended for complicated infections (e.g. pneumonia complicated by empyema or infective endocarditis) and for directed therapy to treat certain pathogens such as Mycobacterium tuberculosis .…”
Section: Can the Duration Of Antimicrobial Therapy Be Shortened?mentioning
confidence: 99%
“…A systematic review and Bayesian meta-analysis pointed out that a gram stain was adequately accurate to diagnose S. pneumoniae and H. influenzae in those with CAP [29]. With good-quality specimens, it can form a basis of clinical actions for specified antibiotic therapies for certain pathogens.…”
Section: Sputum Gram Stainmentioning
confidence: 99%
“…Five-day treatment and longer antibiotic courses for CAP resulted in similar clinical and microbiological responses and exhibited comparable safety profiles [109]. However, recent analyses pointed out that a shorter treatment duration (3-5 days) probably offers the optimal balance between efficacy and treatment burden for treating CAP in adults if they achieved clinical stability [29].…”
Section: Principles Of Treatmentmentioning
confidence: 99%